Analisis Kinerja dan Strategi Pengelolaan Portofolio Saham Syariah di Indonesia : Kajian Literatur 2019–2024 - Muammar Khaddafi; Nurul Monika Larasati; Mega Yuwanda; Trie Yolanda Sari (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Indonesia’s Islamic capital market has experienced remarkable growth in recent years, evidenced by the increasing number of investors and the rising market capitalization of Sharia-compliant stocks. This article aims to analyze the performance and management strategies of Sharia stock portfolios by reviewing academic literature published in Indonesia between 2019 and 2024. Utilizing a literature review methodology, the study compares the return and risk characteristics of Sharia stocks with those of conventional stocks. It also evaluates the applicability and effectiveness of classical portfolio theories—namely, the Markowitz Model and the Single Index Model—in managing Sharia-compliant investments. The findings reveal that Sharia stock portfolios often perform competitively and tend to exhibit greater resilience and stability during financial crises. This resilience is attributed in part to the rigorous stock screening mechanisms that comply with Islamic principles, excluding sectors and companies that do not meet Sharia criteria. Additionally, various macroeconomic factors such as inflation, interest rates, exchange rates, and global economic fluctuations are found to impact the performance of Islamic stock portfolios. The article highlights that while Sharia investments align with ethical and religious values, they also offer practical advantages in risk management and diversification. Furthermore, digital technology and fintech innovation are seen as essential tools to enhance transparency, accessibility, and investor engagement in the Islamic capital market. The study concludes that the development of Sharia-compliant stock investments in Indonesia holds promising potential, especially if accompanied by improved financial literacy, inclusive investor education, and stronger technological infrastructure. This paper offers valuable insights for policymakers, market regulators, and investors interested in promoting sustainable and faith-based financial practices within Indonesia’s rapidly evolving capital market ecosystem.